Functional Organization of the Sympathetic Pathways Controlling the Pupil: Light-Inhibited and Light-Stimulated Pathways - Szabadi, Elemer (Frontiers in Neurology, 2018)
Pupil dilation is mediated by a sympathetic output acting in opposition to parasympathetically mediated pupil constriction. While light stimulates the parasympathetic output, giving rise to the light reflex, it can both inhibit and stimulate the sympathetic output. Light-inhibited sympathetic pathways originate in retina-receptive neurones of the pretectum and the suprachiasmatic nucleus (SCN): by attenuating sympathetic activity, they allow unimpeded operation of the light reflex. Light stimulates the noradrenergic and serotonergic pathways. The hub of the noradrenergic pathway is the locus coeruleus (LC) containing both excitatory sympathetic premotor neurones (SympPN) projecting to preganglionic neurones in the spinal cord, and inhibitory parasympathetic premotor neurones (ParaPN) projecting to preganglionic neurones in the Edinger-Westphal nucleus (EWN). SympPN receive inputs from the SCN via the dorsomedial hypothalamus, orexinergic neurones of the latero-posterior hypothalamus, wake- and sleep-promoting neurones of the hypothalamus and brain stem, nociceptive collaterals of the spinothalamic tract, whereas ParaPN receive inputs from the amygdala, sleep/arousal network, nociceptive spinothalamic collaterals. The activity of LC neurones is regulated by inhibitory α2-adrenoceptors. There is a species difference in the function of the preautonomic LC. In diurnal animals, the α2-adrenoceptor agonist clonidine stimulates mainly autoreceptors on SymPN, causing miosis, whereas in nocturnal animals it stimulates postsynaptic α2-arenoceptors in the EWN, causing mydriasis. Noxious stimulation activates SympPN in diurnal animals and ParaPN in nocturnal animals, leading to pupil dilation via sympathoexcitation and parasympathetic inhibition, respectively. These differences may be attributed to increased activity of excitatory LC neurones due to stimulation by light in diurnal animals. This may also underlie the wake-promoting effect of light in diurnal animals, in contrast to its sleep-promoting effect in nocturnal species. The hub of the serotonergic pathway is the dorsal raphe nucleus that is light-sensitive, both directly and indirectly (via an orexinergic input). The light-stimulated pathways mediate a latent mydriatic effect of light on the pupil that can be unmasked by drugs that either inhibit or stimulate SympPN in these pathways. The noradrenergic pathway has widespread connections to neural networks controlling a variety of functions, such as sleep/arousal, pain, and fear/anxiety. Many physiological and psychological variables modulate pupil function via this pathway.